2013
DOI: 10.1371/journal.pone.0061467
|View full text |Cite
|
Sign up to set email alerts
|

Behaviours Associated with Acoustic Communication in Nile Tilapia (Oreochromis niloticus)

Abstract: BackgroundSound production is widespread among fishes and accompanies many social interactions. The literature reports twenty-nine cichlid species known to produce sounds during aggressive and courtship displays, but the precise range in behavioural contexts is unclear. This study aims to describe the various Oreochromis niloticus behaviours that are associated with sound production in order to delimit the role of sound during different activities, including agonistic behaviours, pit activities, and reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 53 publications
0
44
1
1
Order By: Relevance
“…Females have been found to produce sounds in 17 cichlid species, but not in T. mariae. 34,35 Hence, although differences in morphology exist within breeding pairs of T. mariae, 16 the sex of both fish were confirmed by autopsy (Table I).…”
Section: A Description Of T Mariae Acoustic Behaviormentioning
confidence: 88%
See 1 more Smart Citation
“…Females have been found to produce sounds in 17 cichlid species, but not in T. mariae. 34,35 Hence, although differences in morphology exist within breeding pairs of T. mariae, 16 the sex of both fish were confirmed by autopsy (Table I).…”
Section: A Description Of T Mariae Acoustic Behaviormentioning
confidence: 88%
“…The observation of female vocalization expand on previous studies on other cichlids, of which females have been found to produce sound in 17 species. 34,35 In T. mariae, males have been documented to vocalize during aggressive male-male interaction. 34,35 The exact role and general occurrence of female vocalization in this and other cichlid species, as well as the mechanism producing the sound, are unclear and require further research.…”
Section: Discussionmentioning
confidence: 99%
“…Many cichlid fishes use sounds for species or individual recognition Verzijden et al 2010;Bertucci et al 2012a;Longrie et al 2013), during territorial or agonistic interactions (Amorim 2006;Simoes et al 2008;Bertucci et al 2012b), and during reproductive courtship contexts (Amorim et al 2003. Cichlids are one of the most visually conspicuous groups of fishes, with complex coloration patterns and elaborate courtship behavioral displays.…”
Section: Acoustic Communication In Cichlidsmentioning
confidence: 99%
“…Thus, visual communication is extremely important in this group, and sounds are likely used as a supplement to this rich visual information, which differs from the case in batrachoidid fishes (toadfish, midshipman) that use acoustic signaling as a primary sensory channel. Descriptions of sound production in cichlids thus far show that sounds are not typically used alone, but are produced concurrent with visual display behaviors (Ripley and Lobel 2004;Longrie et al 2013). …”
Section: Acoustic Communication In Cichlidsmentioning
confidence: 99%
“…A large number of fishes are known to produce sounds in different social contexts such as agonistic interactions, courtship and competitive feeding (Amorim et al, 2003;Amorim and Hawkins, 2005;Amorim and Neves, 2008;Bertucci et al, 2010;Colleye and Parmentier, 2012;Ladich, 1997;Lobel, 1998;Longrie et al, 2013;Parmentier et al, 2010). Sounds produced by males during courtship interactions for instance can affect the choice of female mate (Amorim et al, 2004;Danley et al, 2012;Phillips and Johnston, 2009;Verzijden et al, 2010).…”
Section: Introductionmentioning
confidence: 99%